Pendidikan Humanistik Dalam Perspektif Al-Qur’an - Muhtadi, Mohammad (Al Ashriyyah, 2021)
The concept of humanistic education in the Qur'an contains elements including: a) Human education physically and biologically; b) inner human education and psychology; c) social human education and d) spiritual education. Concepts in the perspective of Al-Qur’an which become the foundation for a humanist education, including: the nature of human form, the potential of humanity, and the purpose of human creation. The humanization applied in the Qur'an does not leave the role of man on earth as its function and role as "imarah al-ardl," and as a servant who is obliged to serve the khalik as his function and role as "ibad." As for education with a paradigm the humanists contained in the Qurʻan are: First, putting back all educational activities (talab al-ilm) under the framework of religious work which aims to seek the pleasure of Allah. Second, there is a comparison between religious knowledge and general knowledge. Third, freedom in developing science. Fourth, reviewing grounded science so that it can be implemented in daily life and start trying to implement an integrative educational strategy. The activities of human life are based on the spiritual dimension so that they do not harm others. This thought emphasizes the development of human potential in order to be able to portray themselves as ‘abd Allah and the khalifah of Allah. This education is intended to help students actualize their potential to become independent and creative people who are aware of God's presence in themselves.